Late Ordovician to earliest Silurian graptolite and brachiopod biozonation from the Yangtze region, South China, with a global correlation - XU, CHEN; JIAYU, RONG; MITCHELL, CHARLES E.; HARPER, DAVID A. T.; JUNXUAN, FAN; RENBIN, ZHAN; YUANDONG, ZHANG; RONGYU, LI; YI, WANG (Geological Magazine, 2000)
Late Ordovician to earliest Silurian is an important geological period marked by large geological and biological events. However, the strata and fossils of this interval are not complete in many parts of the world. Based on studies of 43 sites in South China, in particular the continuous sections on the Yangtze platform, we recognize a complete succession including seven graptolite zones and two shelly faunas. In ascending order, the graptolite zones are the Dicellograptus complanatus , Dicellograptus complexus , Paraorthograptus pacificus (including Lower Subzone, Tangyagraptus typicus Subzone and Diceratograptus mirus Subzone), Normalograptus extraordinarius – Normalograptus ojsuensis , Normalograptus persculptus , Akidograptus ascensus and Parakidograptus acuminatus zones. The shelly faunas are the Foliomena – Nankinolithus and Hirnantia faunas, which may be correlated with D. complanatus Zone and N. extraordinarius – N. ojsuensis to part of N. persculptus zones respectively. The biozonation through this interval from the Yangtze region can be correlated with that of other parts of the world such as Dob's Linn in Scotland, Spain and Portugal, Thuringia–Saxonia–Bavaria, Bohemia, Poland, Kazakhstan, Kolyma, Malaya Peninsula, Yukon, Canadian Arctic Islands, Nevada, Argentina, Niger and Victoria, Australia. The Hirnantian Substage, which has been proposed by us recently, includes the N. extraordinarius – N. ojsuensis Zone, Hirnantia fauna and N. persculptus Zone. The base of the Hirnantian Substage is marked by the First Appearance Data (FADs) of N. extraordinarius and N. ojsuensis , which have been determined to be synchronous on a global scale.